PENATALAKSANAAN FISIOTERAPI DENGAN MODALITAS MICROWAVE DIATHERMY DAN CODMAN PENDULUM EXERCISE PADA FROZEN SHOULDER - Tatulus, Yosua H.; Pombu, Novtiyas Maria (Lasalle Health Journal, 2023)
ABSTRACT Introduction: Frozen shoulder, which is a pathological condition or damage in the shoulder joint area that causes pain and results in limited scope of motion of the joint in the shoulder area. Objective: Knowing the implementation of physiotherapy using microwave diathermy and codman pendulum exercises in reducing pain and increasing the scope of joint motion in frozen shoulder sufferers. Methods: a case study conducted on a 62-year-old respondent with complaints of pain in the right shoulder. Results: After receiving physiotherapy treatment using microwave diathermy and codman pendulum exercise 6 times the therapy evaluated using visual analoque scale and goniometer found good results in reducing the degree of pain felt by patients where in the first therapy still pain 2, pressure pain 6 and motion pain 7 became still pain 2, pressure pain 3 and motion pain 4 in the sixth therapy. As well as in the scope of joint motion patients experienced an increase in T1 S: 50º-0º-180º, F: 40º-0º-50º and R: 30º-0º-60º to T6 S:50º-0º-180º, F: 80º-0º-50º and R: 50º-0º-80º. Conclusion: With the treatment of physiotherapy using microwave diathermy and codman pendulum exercise as much as 6 times the therapy found the result of reducing the degree of pain and increasing the scope of motion of the shoulder joint. Keywords: Codman Pendulum Exercise; Frozen shoulder; Microwave Diathermy; Pain; Range of Motion.